Rekonsiliasi Konflik Sosial Pasca Putusan Mahkamah Agung Cabut Izin Tambang: Studi Izin Tambang Batu Gamping di Kampung Lengko Lolok Desa Satar Punda Kecamatan Lamba Leda Kabupaten Manggarai Timur - Fransiskus Alfendi Ance; Yohanes Jimmy Nami; Diana S. A. N Tabun (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Social conflicts arising from differences in interests and perspectives over natural resource management frequently leave long-term social consequences despite formal legal settlements. This study examines the dynamics of social relations in Lengko Lolok Village following the Supreme Court's decision to revoke the limestone mining permit granted to PT Istindo Mitra Manggarai. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observation, and document analysis, and analyzed using John Paul Lederach's conflict transformation theory, which emphasizes the transformation of relationships, interaction patterns, power structures, and perceptions. The findings indicate that the mining policy generated both vertical conflicts between the government and local communities and horizontal conflicts within the community itself. Although the Supreme Court annulled the mining permit, legal resolution did not automatically restore social cohesion. Instead, reconciliation emerged through customary mechanisms and community-driven initiatives based on mutual dependence and shared cultural values. Nevertheless, the transformation process remains incomplete because distrust, political polarization, and avoidance of discussions regarding the root causes of the conflict continue to persist. Consequently, post-conflict conditions in Lengko Lolok reflect partial conflict transformation rather than comprehensive reconciliation, leaving the potential for latent conflict if sustained social reconciliation efforts are not strengthened.